Exploration of Self in the Study of Kamla Das’ the Decedents: An Exploration of Self and Society Through Kamala Das' The Decedents (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper is an attempt of to understand the vision of Kamala Das' poem named The Decedents from the feministic point of view. In a number of Das' poetry, there is an intense voice of self and sufferings. The poems are not only a mirror of her own world but also a kind confronts with society which is primarily a patriarchal in nature. The sensitivity and emotions flowed in the present poem is enough to understand the ceaseless boundaries of emotive senses.